2022
DOI: 10.1111/ijpo.12962
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for engaging in or avoiding conversations about weight: Adolescent and parent perspectives

Abstract: Summary Background Little is known about parent and adolescent motivations for engaging in weight communication. Objectives To assess parent and adolescent motivations for engaging in, or avoiding, weight communication, and whether these reasons differed across sex, race/ethnicity, weight, and engagement in weight management. Methods Independent samples of parents (N = 1936) and unrelated adolescents (N = 2032) completed questionnaires assessing their agreement with different reasons they engage in, or avoid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 47 publications
(81 reference statements)
3
25
0
Order By: Relevance
“…The present study found that more frequent comments from mothers about weight/shape and eating was a significantly predictive factor of EDCs and psychological distress, and that gendered effects were more pronounced with daughters [ 5 , 8 , 20 , 29 ]. However, this was not the case for quality of life, where mothers’ communications appeared to become protective and associated with increased quality of life.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The present study found that more frequent comments from mothers about weight/shape and eating was a significantly predictive factor of EDCs and psychological distress, and that gendered effects were more pronounced with daughters [ 5 , 8 , 20 , 29 ]. However, this was not the case for quality of life, where mothers’ communications appeared to become protective and associated with increased quality of life.…”
Section: Discussionmentioning
confidence: 55%
“…Parents have been found to be key influences during childhood setting standards for behaviour that continue into adult life [ 1 , 2 , 3 ]. Whilst parental influence can diminish in middle adolescence [ 4 , 5 , 6 ], it has been found to have an enduring influence on physical and mental health outcomes with adolescents, particularly for eating disorder cognitions (EDCs), setting longer term foundations of communication and behaviours relating to eating, weight, and shape [ 5 , 7 , 8 ]. Adolescence is also a key life-stage for the onset of eating disorder risk factors, including body dissatisfaction, low self-esteem, and weight shape concerns [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations